2012
DOI: 10.1890/11-0338.1
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects of long‐term land‐use changes on plant traits and ecosystem functioning

Abstract: There is much concern that the functioning of ecosystems will be affected by human-induced changes in biodiversity, of which land-use change is the most important driver. However, changes in biodiversity may be only one of many pathways through which land use alters ecosystem functioning, and its importance relative to other pathways remains unclear. In particular, although biodiversity-ecosystem function research has focused primarily on grasslands, the increases in agricultural inputs (e.g., fertilization, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 65 publications
(130 reference statements)
7
137
1
1
Order By: Relevance
“…Specifically, MRM regresses a response matrix on any number of explanatory matrices composed of dissimilarities or distances, allowing for the inference of how differently measured multi-or univariate variables might influence each other across environmental and spatial distances [27]. Previous studies have proven path modelling to be a highly effective tool for disentangling the complex causal relationships among environmental change, community attributes and ecosystem functioning [28,29]. Here, we use Shipley's [30] d-separation method of generalized causal path analysis, as this method is highly flexible for using a variety of model types, such as MRMs in this case.…”
Section: (D) Constructing Path Models Based On Distance Matricesmentioning
confidence: 99%
“…Specifically, MRM regresses a response matrix on any number of explanatory matrices composed of dissimilarities or distances, allowing for the inference of how differently measured multi-or univariate variables might influence each other across environmental and spatial distances [27]. Previous studies have proven path modelling to be a highly effective tool for disentangling the complex causal relationships among environmental change, community attributes and ecosystem functioning [28,29]. Here, we use Shipley's [30] d-separation method of generalized causal path analysis, as this method is highly flexible for using a variety of model types, such as MRMs in this case.…”
Section: (D) Constructing Path Models Based On Distance Matricesmentioning
confidence: 99%
“…Evaluating the effects of aboveground consumers on plant diversity requires measurements of the intensity of herbivory (e.g., the proportion of primary productivity lost to herbivores), so that the effects of herbivory on plant diversity can be compared at different soil fertility levels [35]. However, the intensity of herbivory can be difficult to measure and generally requires herbivore-exclusion approaches (e.g., [36]).…”
Section: Role Of Aboveground Heterotrophsmentioning
confidence: 99%
“…Direct measure of primary production lost to consumers [35] Herbivore exclusion approaches [36] Effects of aboveground consumers on plant diversity depend on nutrient availability [31]; in productive environments, the preferred species are generally the dominant species, thus increasing diversity [ equation modeling (SEM), are well suited to this task, because they enable explicit linkage of theory to data and can test all direct and indirect causal implications that are derived from a conceptual model [6] (Box 3). A key challenge, however, is how to translate a theoretical model into one that can be evaluated quantitatively [6].…”
Section: Percentage Of Npp Consumedmentioning
confidence: 99%
“…Although this study included some important agroecosystem services (e.g., pollination and pest control), it was not specifically focused on agriculture. In a forage production system, Laliberté and Tylianakis [43] showed that resource addition and grazing strongly determine grassland functional trait diversity, which cascades to induce changes in grassland productivity, decomposition, and soil carbon sequestration. Abiotic and biotic factors directly impacted functional diversity, directly impacted ecosystem functioning, and indirectly impacted ecosystem functioning through changes in functional diversity.…”
mentioning
confidence: 99%